The Effectiveness of Quick on the Draw Technique in Teaching Reading Recount Text - Lailin Nadhifah; Ima Chusnul Chotimah (Penerbit STKIP PGRI Bangkalan, 2018)
Reading is crucial learning activity which mostly makes students bored. To build interactive activity, Quick on the Draw (QOTD) is useful technique that group working is the prior aspect should be done by the students. So that, the researcher interested to investigate whether the students taught by using QOTD have better achievement in reading recount text than the students taught by conventional technique in SMP Negeri 2 Megaluh. This research used quasi experimental design especially nonequivalent control group design which experimental and control group are included. By giving the same pre-test and post-test and different teaching learning process, the research data was collected. The data was analyzed by using ANCOVA SPSS 16.0. By calculating the post-test for both control and experimental group, it was gained F value 6.009. It was meant 6.009 >4.03, the F value is greater than F critical value. And the significance value was 0.018 which is lower than the significance level, 0.018 < 0.05. It could be concluded that Quick on the Draw is effective in teaching reading recount text at the eight students of SMP Negeri 2 Megaluh and the Hypothesis Alternative (Ha) was accepted.